Implementasi Bentuk Kegiatan Pembelajaran Riset - Irwan Ramli; Nurasia Nurasia; Khaerati Khaerati (Jurnal Studi Guru dan Pembelajaran, 2022)
The purpose of this research is to find out about implementing the form of research learning activities at Cokroaminoto Palopo University. The type of research used is literature study research related to how research learning activities form concerning the implementation of Independent Learning Campus Merdeka (MBKM). The focus of this research consisted of two namely 1) The Design of MBKM in the biology education study program of the Teaching and Education Faculty of Cokroaminoto Palopo University and 2) MBKM Policy at College of Cokroaminoto Palopo University. The MBKM design based on scientific research in the Biology Education study program includes the following: 1) Determination of learning outcomes, 2) Learning activities, 3) Evaluation system and 4) Study load. Cokroaminoto Palopo University is contained in the Handbook for the implementation of MBKM within the scope of Cokroaminoto Palopo University. General policies regarding the implementation of MBKM include 1) Free Student Exchange (PMM), 2) Apprenticeship/work practice based on experiential learning, 3) Teaching assistance in educational units, 4) Humanitarian projects, 5) Entrepreneurial activities, 6) Independent Studies, 7) Thematic Field Work Lecture (KKN-Thematic) is an effort to build villages and 8) research. The resylts of the research is Cokroaminoto Palopo University has developed and implemented a curriculum oriented to the Indonesian National Qualifications Framework (KKNI) regulated in Permendikbud RI No. 73 of 2013 concerning the Application of the Indonesian National Qualifications Framework in the Field of Higher Education